Effect of temperature and use of pectinase on apple juice clarification - Unuk, Tatjana (Anali PAZU, 2022)
In year 2009 the experiment was set up at the Faculty of agriculture and life sciences to determine the influence of temperature and enzyme pectinase on apple juice cv. ‘Topaz’ clarification. Treatments represent combinations of different dosage of pectinase (Pektineze XXl; 0,1 ml/l and 0,05 ml/l) and temperature (7 ºC, 12 ºC, 20 ºC) in time of juice clarification. The measurements of juice turbidity were carried out in 30 min intervals, started immediately after and ended 1020 min after press. The results showed negligible influence of temperature on juice clarification. The add of pestinase significantly influenced the clarification, regardless of its dosage (0,5 or 1 dl/1000 l).